RESPONSIBILITIES AND AUTHORITY OF THE PIONEER OFFICERS AND THE PORT AUTHORITY MASTER'S OFFICE IN ENSURING SHIPPING SAFETY AND SECURITY BASED ON LAW NUMBER 17 OF 2008 CONCERNING SHIPPING IN BELAWAN PORT - Riza Firdaus; Dahlan; Henry Aspan (Journal of International Islamic Law, Human Right and Public Policy, 2024)
KSOP has considerable authority in carrying out the function of shipping safety and security including supervising ship pilotage and towing activities in port waters and shipping lanes as stated in Article 207 & 208 paragraph 1, Law 17 of 2008. In carrying out its duties, namely providing instructions and information needed by the Captain or ship leader and assisting in the movement of the ship from the outer threshold/anchorage area to move in/out of Belawan Port, the Pilot Officer is guided by the laws and regulations governing shipping and KSOP as a pilotage supervisor. How is the implementation of the responsibilities and authorities of the Pilot Officer and KSOP in ensuring shipping safety and security at Belawan Port? What are the sanctions given by the Main KSOP Belawan to Pilot Officers who are negligent in carrying out their duties resulting in ship accidents? The research method used in this study is empirical legal research. The research was conducted by examining primary and secondary data in the form of interviews, direct observations in the field, library materials, primary legal materials, secondary and tertiary legal materials. Based on all the data obtained, it is then processed systematically and qualitatively to produce descriptive analytical writing. In this case, the researcher conducted an empirical legal study to see the responsibility and authority of the Pilot Officer and KSOP in ensuring the safety and security of shipping at Belawan Port which is implemented through the Shipping Law & Derivative Regulations governing Ship Pilotage and Delay, where in its implementation the sanctions given by the Pilotage Supervisor (KSOP) do they have a deterrent effect on the professionalism of the Pilot Officer in carrying out their duties.